2010
DOI: 10.1103/physrevlett.104.087003
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Induced Static Magnetic Order in SuperconductingFeSe1x

Abstract: We report on a detailed investigation of the electronic phase diagram of FeSe1-x under pressures up to 1.4 GPa by means of ac magnetization and muon-spin rotation. At a pressure 0.8 GPa the nonmagnetic and superconducting FeSe1-x enters a region where static magnetic order is realized above Tc and bulk superconductivity coexists and competes on short length scales with the magnetic order below Tc. For even higher pressures an enhancement of both the magnetic and the superconducting transition temperatures as w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
246
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(281 citation statements)
references
References 28 publications
(32 reference statements)
32
246
1
2
Order By: Relevance
“…We note the non-monotonous temperature dependence of the magnetic fraction for Ba 0.35 Rb 0.65 Fe 2 As 2 . V m increases below 75 K. This kind of T -dependence of V m was previously observed in a number of Fe-HTS's 63,64 with the static magnetism and may be caused by the interplay between magnetism and superconductivity.…”
Section: A Magnetization and Specific Heat Capacity Experimentsmentioning
confidence: 64%
“…We note the non-monotonous temperature dependence of the magnetic fraction for Ba 0.35 Rb 0.65 Fe 2 As 2 . V m increases below 75 K. This kind of T -dependence of V m was previously observed in a number of Fe-HTS's 63,64 with the static magnetism and may be caused by the interplay between magnetism and superconductivity.…”
Section: A Magnetization and Specific Heat Capacity Experimentsmentioning
confidence: 64%
“…Polycrystalline samples of FeSe 1−x were investigated in early NMR measurements and muon-spin rotation (µSR) experiments. [34][35][36] According to these results, the spin fluctuation is enhanced at pressures up to ∼2.2 GPa 34) and a pressure-induced antiferromagnetic ordered state is stabilized above ∼1 GPa. 35,36) More recent studies on single crystals revealed the comprehensive and complex T -P phase diagram from macro-and microscopic measurements under high pressure.…”
Section: Introductionmentioning
confidence: 94%
“…This behavior is similar to that already observed earlier both by dc and ac magnetization. 8,12,13 In the region where T c decreases static magnetism develops in the sample and competes with superconductivity (see below and Ref. 8).…”
Section: Superconducting Propertiesmentioning
confidence: 99%
“…In fact, static magnetic ordering was observed above p ∼ 0.8 GPa by means of µSR. 8 The experiments revealed that as soon as magnetic ordering occurs, the magnetic and the superconducting states seem to compete with each other. This is because the incommensurate magnetic order gets suppressed when superconductivity sets in and, in addition, T c decreases in the pressure region 0.8 ≤ p ≤ 1.2 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation